PERANAN KYAI DAN SANTRI DALAM MENGIMPLEMENTASIKAN NILAI PENDIDIKAN AGAMA DITENGAH LAJUNYA ARUS GLOBALISASI DAN FENOMENA AKULTURASI BUDAYA INDONESIA - Abdur Rahman Adi Saputera; Meyer Tendean (Fakultas Agama Islam Universitas Islam Madura, 2020)
The phenomenon of diversity behavior that occurs among internal religious communities, especially in Indonesia so far, has indicated a form of political-ideological and legal-formal diversity. Thus the typology of the diversity that exists in Indonesia can easily be labeled with relatively permanent symbols and characters. Intellectual intelligence without emotional and spiritual intelligence will only end in negative behavior. This situation is the background why the teachings and educational traditions that exist in traditional pesantren even though it looks classic and simple still has its own attraction for the initiators of education. On this basis, the spirit of the pesantren education tradition by the initiators and practitioners of education is to be integrated into general education. In short, the traditional pesantren education model cannot be separated from the sincere intentions of a kyai. The role of the kyai, santri as the elite of the Islamic religion towards tradition has made some religious teachings into culture, this effort seeks to be implemented through positive educational values ​​of pesantren.